Alimentos Guarani Mbyá: uma revisão integrativa - Andrade, Isabella Polli Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The Guarani Mbyá food is endowed with symbolic aspects that show its cosmological and ethnic identity. Understanding the eating habits of this group can clarify questions about territorial and agricultural dynamics. This work aims to summarize the information available in the literature on the food produced and/or consumed in Mbyá villages in Latin America, based on the methodology of integrative bibliographic review. The ways of obtaining food, ways of cultivation and survey of the represented species were analyzed, in addition to the incidence of ethnovarieties. The food diversity found gave the dimension of the role of combating the cultural and economic hegemony imposed by non-indigenous people, in addition to the socio-environmental consequences and sequels experienced by the communities. It appears that the Mbyá Guarani way of life ensures the preservation of biodiversity, and it is important to highlight this relationship in order to extinguish the preservationist logic that purges these peoples from their ancestral territories with biased arguments. From this conception, it is possible to establish cooperation with non-indigenous people in the interest of an ecologically balanced environment stipulated by the Brazilian Federal Constitution.

A alimentação Guarani Mbyá é dotada de aspectos simbólicos que evidenciam sua identidade cosmológica e étnica. A compreensão dos hábitos alimentares deste grupo pode elucidar questões sobre dinâmicas territoriais e agrícolas. Este trabalho objetiva a sumarização das informações dispostas na literatura sobre os alimentos produzidos e/ ou consumidos nas aldeias Mbyá na América Latina a partir da metodologia da revisão bibliográfica integrativa. Foram analisadas as formas de obtenção dos alimentos, formas de cultivo e levantamento das espécies representadas, além da incidência de etnovariedades. A diversidade de alimentos constatada deu a dimensão do papel do combate à hegemonia cultural e econômica imposta pelos não indígenas, além das consequências e sequelas socioambientais vividas pelas comunidades. Constata-se que o modo de vida Mbyá Guarani assegura a preservação da biodiversidade, sendo relevante evidenciar esta relação a fim de extinguir a lógica preservacionista que expurga estes povos de seus territórios ancestrais com argumentos enviesados. A partir desta concepção, possivelmente pode-se estabelecer cooperações com os não indígenas para o interesse afim de um meio ambiente ecologicamente equilibrado estipulado pela Constituição Federal brasileira.
Guarani Mbyá foods in Latin America: an integrative review
Keywords: Guarani Mbyá; Alimentação; Soberania; Povos indígenas; Meio ambiente